WRITING A SCIENTIFIC PAPER FOR PUBLICATION AND PUBLICATION ETHICS - Redaksi Team (Majalah Keperawatan Unpad)
Why Do We have to Write?•Complete assignments for assessment •Share ideas and expertise •Disseminate the research findings •Promote career, academic work •Expand knowledge and skills •Gain personal satisfaction